Sex-differences in COPD: from biological mechanisms to therapeutic considerations - Milne, Kathryn M.; Mitchell, Reid A.; Ferguson, Olivia N.; Hind, Alanna S.; Guenette, Jordan A. (Frontiers in Medicine, 2024)
Chronic obstructive pulmonary disease (COPD) is a heterogeneous respiratory condition characterized by symptoms of dyspnea, cough, and sputum production. We review sex-differences in disease mechanisms, structure-function-symptom relationships, responses to therapies, and clinical outcomes in COPD with a specific focus on dyspnea. Females with COPD experience greater dyspnea and higher morbidity compared to males. Imaging studies using chest computed tomography scans have demonstrated that females with COPD tend to have smaller airways than males as well as a lower burden of emphysema. Sex-differences in lung and airway structure lead to critical respiratory mechanical constraints during exercise at a lower absolute ventilation in females compared to males, which is largely explained by sex differences in maximum ventilatory capacity. Females experience similar benefit with respect to inhaled COPD therapies, pulmonary rehabilitation, and smoking cessation compared to males. Ongoing re-assessment of potential sex-differences in COPD may offer insights into the evolution of patterns of care and clinical outcomes in COPD patients over time.